The Impact of Reference Norms on Inflation Persistence When Wages are Staggered - Markus Knell; Alfred Stiglbauer (Oesterreichische Nationalbank (OeNB), 2009)
In this paper we present an extension of the Taylor model with staggered wages in which wage-setting is also influenced by reference norms (i.e. by benchmark wages). We show that reference norms can considerably increase the persistence of inflation and the extent of real wage rigidity but that these effects depend on the definition of reference norms (e.g. how backward-looking they are) and on whether the importance of norms differs between sectors. Using data on collectively bargained wages in Austria from 1980 to 2006 we show that wage-setting is strongly influenced by reference norms, that the wages of other sectors seem to matter more than own past wages and that there is a clear indication for the existence of wage leadership (i.e. asymmetries in reference norms).
Keywords: E31; E32; E24; J51; 330; Inflation Persistence; Real Wage Rigidity; Staggered Contracts; Wage Leadership